Upregulation of Soluble HLA-G5 and HLA-G6 Isoforms in the Milder Histopathological Stages of Helicobacter pylori Infection: A Role for Subverting Immune Responses? - Oliveira Souza, D. M. B.; Genre, J.; Alves Silva, T. G. [UNESP]; Soares, C. P. [UNESP]; Borges Ferreira Rocha, K.; Nunes Oliveira, C.; Nunes Jatoba, C. A.; Marco de Leon Andrade, J.; Moreau, P.; Cunha Medeiros, A. da; Donadi, E. A.; Oliveira Crispim, J. C. de (Wiley-Blackwell, 2016)
The subversion mechanisms employed by Helicobacter pylori (H.pylori) to escape from immune surveillance and to establish persistent infection are poorly understood. Growing evidence indicates that expression of HLA-G, a non-classical major histocompatibility complex molecule, negatively regulates immune responses in pathological conditions, including infectious diseases. In this context, we aimed to evaluate HLA-G expression in the gastric microenvironment of individuals harbouring H.pylori and to correlate it with histological variables. Fifty-four gastric specimens from patients harbouring H.pylori infection were evaluated by immunohistochemistry using anti-HLA-G monoclonal antibody. As a result, HLA-G expression was detected in 43 of 54 specimens harbouring H.pylori. The presence of HLA-G was significantly associated with milder colonization by H.pylori (P<0.02), milder inflammatory activity (P<0.02) and bacterium histological location in the gastric antrum. This study is the first to explore HLA-G expression in the context of bacterial infection. Whether the biological role of HLA-G during H.pylori infection is beneficial or hazardous for patients remains to be defined.